MNDO and DFT Computational Study on the Mechanism of the Oxidation of 1, 2-Diphenylhydrazine by Iodine. (27th March 2014) - Shallangwa, Gideon A.; Uzairu, Adamu; Ajibola, Victor O.; Abba, Hamza
Abstract : The reaction mechanisms of the oxidation of 1, 2-diphenylhydrazine by iodine have been examined using semiempirical and density functional theory methods, the oxidation proceeded via two independent pathways that can be separately monitored. One pathway involved the chain multistep mechanism. The other pathway occurred via a one-step mechanism in which a "cyclic" activated complex was formed which on disproportionation gave the products. The one-step "cyclic" activated complex mechanism proceeds more rapidly than the chain multistep mechanism. The results were explained by analyses based on computational energetics of the optimised reactants, intermediates, transition states, and products of the reaction of iodine with 1, 2-diphenylhydrazine.